Arab Liberation Movements During the Two World Wars: A Simplified Reading of Recent Writings - Areej Abdul Karim Mohammed Al-Amri (Academia Open, 2026)
General Background: The Arab region experienced profound political transformations during the First and Second World Wars, shaping the emergence of liberation movements and modern national consciousness. Specific Background: The collapse of the Ottoman Empire, the rise of the Great Arab Revolt, and the imposition of the mandate system in Iraq and the Levant framed the trajectory of Arab nationalist struggles, later reinforced by the weakening of European colonial powers during the Second World War. Knowledge Gap: Existing studies vary in interpreting these movements, whether as outcomes of internal social and intellectual developments or responses to international geopolitical shifts, necessitating a synthesized analytical reading. Aims: This article aims to provide a simplified analytical review of recent writings on Arab liberation movements, focusing on their historical development, interpretive approaches, and interaction with global powers. Results: The findings indicate that Arab liberation movements emerged through a combination of intellectual awakening, socio-political mobilization, and international transformations, manifested in political organizations, revolutions, and resistance against Ottoman and colonial authorities, ultimately contributing to the gradual independence of Iraq and Syria. Novelty: The study offers an integrated perspective linking internal dynamics of Arab nationalist thought with external geopolitical changes through a descriptive-analytical synthesis of recent scholarship. Implications: These insights contribute to a deeper understanding of the formation of modern Arab states and highlight the significance of sustained national resistance in shaping political sovereignty within both regional and international contexts. Highlights: • Intellectual Elites and Print Media Accelerated Early Nationalist Awareness• Diverse Resistance Strategies Ranged From Reformist Discourse to Armed Uprisings• Colonial Agreements Exposed Contradictions Between External Agendas and Regional Aspirations Keywords: Arab Liberation Movements, Arab Nationalism, World Wars, Mandate System, Independence Trajectories.